1997
DOI: 10.1111/j.1460-9568.1997.tb01698.x
|View full text |Cite
|
Sign up to set email alerts
|

The ExDression Pattern of the Orphan Nuclear Receptor RORβ in the Developing and Adult Rat Nervous System Suggests a Role in the Processing of Sensory Information and in Circadian Rhythm

Abstract: RORbeta is an orphan nuclear receptor related to retinoid and thyroid hormone receptors and is exclusively expressed in the central nervous system (CNS). Here we present an in situ hybridization analysis of the distribution of RORbeta mRNA in the developing and adult rat CNS. The receptor localizes to areas involved in the processing of sensory information. In the cerebral cortex, RORbeta mRNA was exclusively detected in non-pyramidal neurons of layer IV and, less so, layer V. The highest expression was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
109
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 25 publications
(17 reference statements)
17
109
0
Order By: Relevance
“…We next examined the expression profile of Rorb in detail, as this protein is well known to be specifically expressed in L4 neurons of the mature neocortex (13,14). Interestingly, Rorb expression on E16.5 and E18.5 was mainly restricted to LCP neurons, as judged by almost no [on E16.5 ( Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…We next examined the expression profile of Rorb in detail, as this protein is well known to be specifically expressed in L4 neurons of the mature neocortex (13,14). Interestingly, Rorb expression on E16.5 and E18.5 was mainly restricted to LCP neurons, as judged by almost no [on E16.5 ( Fig.…”
Section: Significancementioning
confidence: 99%
“…Rorb belongs to the orphan nuclear receptor family and is preferentially expressed in L4 of the mature neocortex (13,14). Brn1/2 are members of the class III POU (Pit1-Oct1/Oct2-UNC86) domain transcription factors and are preferentially expressed in L2/3 and L5 of the mature neocortex (15-17).…”
mentioning
confidence: 99%
“…Levels of RORβ mRNA were determined by competitive RT-PCR and normalized to total RNA. published in situ hybridization data (Schaeren-Wiemers et al, 1997).…”
Section: Generation Of Transgenic Mice Carrying Rorβ Null Allelesmentioning
confidence: 99%
“…Rorb is expressed in all neural retina layers from early stages with a peak at neonatal stages, suggestive of a role in many differentiating retinal cell types including both cones and rods (21)(22)(23). We previously reported that Rorb and Crx synergistically induce the S opsin promoter (24), indicating a role for Rorb in cone differentiation.…”
mentioning
confidence: 94%